Capturing an initial intermediate during the P450nor enzymatic reaction using time-resolved XFEL crystallography and caged-substrate. Issue 1 (December 2017) - Tosha, Takehiko; Nomura, Takashi; Nishida, Takuma; Saeki, Naoya; Okubayashi, Kouta; Yamagiwa, Raika; Sugahara, Michihiro; Nakane, Takanori; Yamashita, Keitaro; Hirata, Kunio; Ueno, Go; Kimura, Tetsunari; et al.
Abstract Time-resolved serial femtosecond crystallography using an X-ray free electron laser (XFEL) in conjunction with a photosensitive caged-compound offers a crystallographic method to track enzymatic reactions. Here we demonstrate the application of this method using fungal NO reductase, a heme-containing enzyme, at room temperature. Twenty milliseconds after caged-NO photolysis, we identify a NO-bound form of the enzyme, which is an initial intermediate with a slightly bent Fe-N-O coordination geometry at a resolution of 2.1 Å. The NO geometry is compatible with those analyzed by XFEL-based cryo-crystallography and QM/MM calculations, indicating that we obtain an intact Fe3+ -NO coordination structure that is free of X-ray radiation damage. The slightly bent NO geometry is appropriate to prevent immediate NO dissociation and thus accept H− from NADH. The combination of using XFEL and a caged-compound is a powerful tool for determining functional enzyme structures during catalytic reactions at the atomic level. Using photosensitive caged-compound for femtosecond crystallography at X-ray free electron lasers would allow the structure determination of reaction intermediates. Here the authors demonstrate the feasibility of this approach with a caged NO-compound and present the initial NO-bound intermediate structure of cytochrome P450 nitric oxide reductase.